Competition and distance to the technological frontier as determinants of innovation: A multilevel analysis for Latin America - Ezequiel Tacsir; Mariano Pereira; Federico Favata; Julian Leone (Inter-American Development Bank (IDB), 2024)
Using a multilevel analysis and the new Harmonized Latin American Innovation Surveys Database (or LAIS database) augmented with indicators from the U.S. Census Bureau's Survey of Business Owners (SBO) and the World Banks World Integrated Trade Solution (WITS), this paper presents estimates of the effects of import competition and distance to the technological frontier on firm innovation in Latin American countries. Although innovation is recognized as a multilevel phenomenon, with investment decisions not solely affected by the firm characteristics but also by the context in which each firm is embedded, the empirical literature adopting a multilevel design is still nascent and scarce. Using a two-level random slope model allows us to overcome some of the pitfalls of traditional regression models when dealing with the hierarchical structure of data while allowing us to capture the influence of contextual factors. The results suggest that the fostering effect of foreign competition depends on the firms distance to the technological frontier. The estimates suggest that the lower the foreign competition and the greater the productivity gap, the lower the probability of firms engaging in innovation. In contrast, when a firm operates in a sector that is relatively closer to the technological frontier, firms invest in innovative activities to remain at the top. These results offer a clear and useful guide for designing policies in Latin America regarding innovation among firms. While it is important to promote and stimulate innovation efforts by firms, these factors should not be overlooked as considerations: sectoral characteristics associated with the economies, sectoral openness to foreign competition, and firms distance to the technological frontier.
Keywords: O31; O32; C21; C25; 330; innovation; Latin America; multilevel modeling; LAIS database; productivity; competition